PIEZO1 functions as a potential oncogene by promoting cell proliferation and migration in gastric carcinogenesis. Issue 9 (2nd May 2018) - Zhang, Jinglin; Zhou, Yuhang; Huang, Tingting; Wu, Feng; Liu, Liping; Kwan, Johnny S. H.; Cheng, Alfred S. L.; Yu, Jun; To, Ka Fai; Kang, Wei
Abstract : Gastric cancer (GC) is one of the most common malignancies in Asian areas. PIEZO1 has been implied to regulate epithelial homeostasis to play an important role in physiological processes. It is also related to tumor initiation and progression. However, the role of PIEZO1 has not yet been explored in GC. The expression of PIEZO1 in GC cell lines and primary samples was determined by qRT‐PCR and Western blot. The clinical correlation of PIEZO1 in GC was evaluated by immunohistochemistry on tissue microarray. The oncogenic role of PIEZO1 was demonstrated in gastric tumorigenesis through a series of functional assays, including cell proliferation, cell invasion, and flow cytometry analysis. Drug sensitivity was also assessed by PIEZO1 knockdown experiment. PIEZO1 exhibited an upregulation in most of the GC cell lines and primary samples compared with non‐tumorous gastric epithelial tissues. Increase of PIEZO1 was associated with poor disease specific survival. PIEZO1 knockdown led to inhibitory effect by suppressing cell proliferation and invasion and inhibiting xenograft formation. Decreased PIEZO1 enhanced the sensitivity of Cisplatin or 5‐FU treatment. Morphological alteration was also observed in siPIEZO1 treated cells. GTP‐Rac1 showed accumulated activated form, while total‐RhoA was decreased accompanied with PIEZO1 knockdown. In the present study, PIEZO1 is required for cell proliferation, migration and invasion to promote GC progression. PIEZO1 also maintains cellular morphology related to GC cell motility by regulating the activity of Rho GTPase family members. Our data not only suggested a novel prognostic marker, but also provided a useful clinical therapeutic target for GC.